Divergent artificial selection for female reproductive investment has a sexually concordant effect on male reproductive success. Issue 4 (23rd August 2017) - Pick, Joel L.; Hutter, Pascale; Tschirren, Barbara
Abstract: Depending on the genetic architecture of male and female fitness, sex‐specific selection can have negative, positive, or neutral consequences for the opposite sex. Theory predicts that conflict between male and female function may drive the breakdown of intrasexual genetic correlations, allowing sexual dimorphism in sexually antagonistic traits. Reproductive traits are the epitome of this, showing highly differentiated proximate functions between the sexes. Here we use divergent artificial selection lines for female reproductive investment to test how female‐specific selection on a sex‐limited trait affects male reproductive success in a precocial bird, the Japanese quail ( Coturnix japonica ). We demonstrate that selection for increased egg investment in females positively affects male reproductive success both in competitive and non‐competitive mating situations. This increased reproductive success was linked to a relatively larger left testis in males originating from lines selected for high female reproductive investment. Given that female quail have functional gonads only on their left side, this correlated response indicates that selection has acted on the shared developmental basis of male and female gonads. Our study thereby provides evidence for a positive genetic correlation between key reproductive traits in males and females despite a high degree of sexual dimorphism, and suggests that, in this system, selection on reproductive function is sexually concordant.